Identifikasi Batas Wilayah Dan Infrastruktur Desa Kubang Utara Sikabu Melalui Peta Administrasi - Sandra Dewi; Neza Fatika; Tiara Safitri; Pyona Faddila Najmi; Qori Dwi Kemala (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Artikel Kubang Utara Sikabu Village, located in Kecamatan Lembah Segar, has clear boundaries and diverse infrastructure. This research aims to identify village boundaries and infrastructure through administrative maps. The methods used included administrative map analysis and field data collection to map the boundaries and existing infrastructure. The results of the analysis show that Kubang Utara Village has an area of 1,156 hectares with defined boundaries, and education and health infrastructure that still needs to be improved. These findings provide important information for the village government in development planning, resource management and improving the quality of life of the community. The resulting administrative map can be used as a tool for more effective infrastructure planning and development.